Preparing for the Philosophical Challenges of Digital Technoscience: “Philosophy in Technology” for Modern Engineering Teaching - Polak Paweł (Studies in Logic, Grammar and Rhetoric)
The article presents philosophical challenges to the development of modern technoscience in the context of engineering education. We use the term technoscience because modern technology not only makes extensive use of the results of science, but also applies elements of scientific methodology. We find many philosophical issues in technology, but their influence is particularly evident in modern technoscience. Hence the question of how to prepare engineers for the rapid development of technoscience and the growing role of philosophy. To this end, it was proposed to introduce philosophy as one of the pillars of engineering education and to base philosophical education on the concept of “philosophy in technology”. Why this concept is extremely useful for engineers is justified, allowing them to be well prepared for the uncertainties associated with the development of technoscience and to stimulate innovation. Concrete proposals for such a curriculum are also indicated.